At the "Five Islands" Trinidad - (:unkn) unknown (Wilsons Ltd.,[Trinidad and Tobago]; Printed in Germany, 2011)
The postcard shows the "Five Islands" which are actually a group of six islands that are located west of Port of Spain, the capital of Trinidad, in the Gulf of Paria. They are also known as Las Cortorras. These are Caledonia Island, Craig Island, Lenagen Island, Nelson Island and Pelican Island.
Colour: Sepia; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Islands--Trinidad and Tobago